Wear behavior of as-cast and heat treated triple particle size SiC reinforced aluminium metal matrix composites - Maleque, Md. Abdul; Karim, Md. Rezaul (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to study the wear behavior of as-cast (AC) and heat treated (HT) triple particle size (TPS) silicon carbide (SiC) reinforced aluminum alloy-based metal matrix composites (SiCp/Al-MMC).